2010
DOI: 10.1107/s1600536810021045
|View full text |Cite
|
Sign up to set email alerts
|

4-(2-Methylanilino)pent-3-en-2-one

Abstract: The title enamino ketone, C12H15NO, a derivative of 4-(phenyl­amino)­pent-3-en-2-one, presents a roughly planar [greatest displacement of an atom from the pentenone plane is 0.033 (2) Å] pentenone backbone, enhanced by an intra­molecular N—H⋯O hydrogen bond; the asymmetry in C—C distances in the group suggests the presence of unsaturated bonds. The overall geometry in the free ligand differs significantly from that in other reported compounds, in which it is coordinated to rhodium; this is reflected in the bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
2
5
0
1
Order By: Relevance
“…Bond distances differ significantly from compounds coordinated to rhodium (Table 2; Venter et al, 2009a,b), such as the distance, N1•••O1, greatly increasing (~0.2 Å) upon coordination to the metal. Similarities in bond parameters to other uncoordinated enaminoketone compounds (Venter et al, 2010) were observed. The C2-C3 distance of 1.385 (2) Å, versus the C3-C4 bond distance of 1.424 (2) Å indicates an unsaturated bond in the pentenone backbone.…”
Section: Data Collectionsupporting
confidence: 73%
See 2 more Smart Citations
“…Bond distances differ significantly from compounds coordinated to rhodium (Table 2; Venter et al, 2009a,b), such as the distance, N1•••O1, greatly increasing (~0.2 Å) upon coordination to the metal. Similarities in bond parameters to other uncoordinated enaminoketone compounds (Venter et al, 2010) were observed. The C2-C3 distance of 1.385 (2) Å, versus the C3-C4 bond distance of 1.424 (2) Å indicates an unsaturated bond in the pentenone backbone.…”
Section: Data Collectionsupporting
confidence: 73%
“…For synthetic background, see: Shaheen et al (2006); Venter et al (2010). For applications of enaminoketones, see: Brink et al (2010); Chen & Rhodes (1996); Pyżuk et al (1993); Roodt & Steyn (2000); Tan et al (2008); Xia et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the use of enamino-ketones in medicine, see: Tan et al (2008); and in catalysis, see: Roodt & Steyn (2000); Brink et al (2010). For background to the ligand preparation, see: Shaheen et al (2006); Venter et al (2010);Venter, Brink et al (2012). For applications of rhodium compounds containing bidentate ligand systems, see: Pyżuk et al (1993); Tan et al (2008); Xia et al (2008).…”
Section: Related Literaturementioning
confidence: 99%
“…The title compound (Fig. 1) is a derivative of 4-(phenylamino)pent-3-en-2-one whose crystal structure has already been published (Shaheen et al, 2006) and forms part of an ongoing investigation on the influence of electron-donating andwithdrawing substituents on the benzene unit of these types of enaminoketones (Table 2; Venter et al, 2010aVenter et al, , 2010b.…”
Section: S1 Commentmentioning
confidence: 99%